Chemical analysis of antibiotic residues in food - Wang, Jian, 1969-; MacNeil, James D.; Kay, Jack F. (Hoboken, N.J. : Wiley & Sons, 2012)
An insightful exploration of the key aspects concerning the chemical analysis of antibiotic residues in food The presence of excess residues from frequent antibiotic use in animals is not only illegal, but can pose serious health risks by contaminating products for human consumption such as meat and milk. Chemical Analysis of Antibiotic Residues in Food is a single-source reference for readers interested in the development of analytical methods for analyzing antibiotic residues in food. It covers themes that include quality assurance and quality control, antibiotic chemical pro.
Antibiotics : groups and properties / Philip T. Reeves -- Pharmacokinetics, distribution, bioavailability, and relationship to antibiotic residues / Peter Lees and Pierre-Louis Toutain -- Antibiotic residues in food, drinking water, and food safety regulations / Kevin J. Greenlees, Lynn G. Friedlander, and Alistair Boxall -- Sample preparation : extraction and clean-up / Alida A.M. (Linda) Stolker and Martin Danaher -- Bioanalytical screening methods / Sara Stead and Jacques Stark -- Chemical analysis : quantitative and confirmatory methods / Jian Wang and Sherri B. Turnipseed -- Single residue quantitative and confirmatory methods / Jonathan Tarbin [and others] -- Method development and method validation / Jack F. Kay and James D. MacNeil -- Measurement uncertainty / Jian Wang [and others] -- Quality assurance and quality control / Andrew Cannavan, Jack Kay, and Bruno Le Bizec.
Includes bibliographical references and index.
Print version record.
Keywords: Veterinary drug residues -- Analysis; Antibiotic residues -- Analysis; Food of animal origin -- Safety measures; Anti-Bacterial Agents -- analysis; Chemistry Techniques, Analytical -- methods; Drug Residues; Food Safety; MEDICAL -- Toxicology; Electronic books